Beyond borders: exploring the impact of augmented reality on intercultural competence and L2 learning motivation in EFL learners - Liu, Song; Gao, Shengbing; Ji, Xiaoyan (Frontiers in Psychology, 2023)
Introduction This mixed-methods study investigates the impact of augmented reality (AR) on the development of intercultural competence and L2 (second language) learning motivation among Chinese English as a Foreign Language (EFL) learners. The research comprised forty-eight intermediate-level learners who were randomly assigned to either an experimental group, receiving AR-based language instruction, or a control group, receiving traditional instruction. Methods Both groups underwent pre- and post-tests to assess their intercultural competence and L2 learning motivation. The experimental group engaged with an AR application, which exposed learners to a variety of cultural scenarios, customs, and norms. Results The results indicate that the experimental group, exposed to AR-based instruction, demonstrated significantly higher levels of intercultural competence and L2 learning motivation in comparison to the control group. Discussion Qualitative data analysis further elucidated that AR-based instruction enhanced learners’ engagement, motivation, and deepened their cultural understanding. This study highlights the potential of augmented reality as a powerful tool for fostering the development of intercultural competence and L2 learning motivation within the EFL context, suggesting promising opportunities for innovative pedagogical approaches in language education.